Women and Scientific Employment - Glover, J. author. aut Link
XI, 190 p. 1 illus.
Keywords: Women and Scientific Employment combines rich empirical data and theoretical discussion on the 'problem' of women's representation in scientific education and employment. A distinction is made throughout between 'quantitative feminization' and 'vertical feminization' - a distinction which is frequently confused in policy on women and the sciences. Comparisons are made with the USA and France, revealing considerable similarity with the UK. The case is put for the different scientific disciplines to be examined separately, both empirically and theoretically.